KECENDERUNGAN PENAMAAN JALAN DI KOTAMADYA DAERAH TINGKAT II SURABAYA - Benny Poerbantanoe (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 1999)
This paper is the result of updating of fact and figures, derived from the draft Master Plan of street names in the IId level municipal area of Surabaya, prepared by the writer when he was making a comparative study in 1996-1997 dealing with result of data drawing and collection from primary sources and secondary sources. It contains an analytical description based on facts, showing the prevaling tendency and pattern of thought in Surabaya, starting from 1706 at a time when the Gemeente of Surabaya was not yet established up to 1998 under the rules of the present IId level municipal governement. In this study is used as yard stick